Preparing the teacher according to Islamic education Between originality and modernity (Journal of the College of Basic Education, 2022)
The human being is the focus of all development efforts through the facts indicated by a lot of research, as well as the means to achieve them, and the process of learning and teaching is truly necessary, and since the teacher at the time is one of the basic pillars of the educational process inside and outside the school, he is the effective element and responsible for Creating their motivation towards attainment and knowledge and building a normal human personality capable of living in an atmosphere of knowledge flow and technical development and dealing with internal and external change factors, which are many psychological, educational, ethical, social, scientific, technical and aesthetic.